Perilaku Mengambil Keputusan Ditinjau dari Psikologi Positif dan Indigenous - Rubiyanti Rubiyanti; Nina Fitriana (EduInovasi: Journal of Basic Educational Studies, 2026)
Decision making is an essential psychological behavior in individual and organizational life as it determines actions and their consequences. This study aims to analyze decision-making behavior from the perspectives of positive psychology and indigenous psychology and to integrate both approaches in understanding decision making within a cultural context. This research employed a literature review method using secondary data obtained from relevant academic journals and scholarly books. Data were analyzed using content analysis to examine key concepts, findings, and theoretical frameworks related to decision making, psychological well-being, and cultural values. The findings indicate that from the perspective of positive psychology, decision making is significantly influenced by individuals’ psychological strengths, such as motivation, emotional intelligence, and self-efficacy, which contribute to more adaptive and meaningful decisions. Meanwhile, indigenous psychology emphasizes that decision making is strongly shaped by cultural values, social norms, and collectivistic orientations, particularly within the Indonesian context. The integration of positive psychology and indigenous psychology provides a more holistic understanding of decision-making behavior, where decisions are not solely evaluated based on goal effectiveness but also on psychological well-being and social harmony. This study highlights the importance of an integrative approach in understanding context-sensitive and sustainable decision-making behavior.